2006
DOI: 10.1158/0008-5472.can-05-1631
|View full text |Cite
|
Sign up to set email alerts
|

Differential Functional Activation of Chemokine Receptor CXCR4 Is Mediated by G Proteins in Breast Cancer Cells

Abstract: CXCR4 is a G protein-coupled receptor of considerable biological significance, and among its numerous functions, it is suggested to play a critical role in cancer metastasis. We have investigated the expression and function of CXCR4 in a range of breast cancer cell lines covering a spectrum of invasive phenotypes and found that, while surface levels of CXCR4 were uniform across the entire panel, only highly invasive cells that are metastatic in immunocompromised mice expressed functional receptors. CXCL12/SDF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 39 publications
6
90
1
2
Order By: Relevance
“…1b. Even though overexpression of CXCR4 in MCF10A cell line has been reported before [26], we could not find in the literature any particular data explaining why the levels of CXCR4 were higher in non-cancerous than in cancerous cells. Moreover, there are no published data about the expression change of CXCR4 in those cell lines with time.…”
Section: Discussioncontrasting
confidence: 80%
“…1b. Even though overexpression of CXCR4 in MCF10A cell line has been reported before [26], we could not find in the literature any particular data explaining why the levels of CXCR4 were higher in non-cancerous than in cancerous cells. Moreover, there are no published data about the expression change of CXCR4 in those cell lines with time.…”
Section: Discussioncontrasting
confidence: 80%
“…3 Blocking the interaction between CXCR4 and its ligand CXCL12, dramatically reduces breast and other cancer metastases in mouse models. 4 Our recent results have also provided a direct correlation between functional activation of CXCR4 and CCR7 and the invasive, metastatic phenotype of breast cancer cells 5 further supporting a highly important role for these molecules in tumor dissemination to distant sites. Initial studies suggested that these surface molecules induce directional migration of malignant cells along chemokine gradients towards secondary tumor sites in a manner that is similar to the process of lymphocyte homing.…”
mentioning
confidence: 54%
“…We found that ligands for both CXCR4 and CCR7 decreased anoikis only in highly invasive, metastatic breast cancer cells but failed to affect apoptosis in untransformed or non-metastatic cells with silent CXCR4 and CCR7. 5 Thus detachment-induced cell death in non-invasive MDA-453 (Figure 2a), MDA-134 and MCF-10A (not shown) cells was not affected by incubation with chemokines and was only reduced by the addition of serum. The selectivity of anoikisreducing function of CXCL12 and CCL21 was further documented by the inability of these chemokines to induce cytotoxic drug resistance.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Loss of E-cadherin expression has been shown to correlate with invasion and metastasis in many types of carcinoma [49]. Madhavan et al [50] reported that the expression of Ecadherin and P-cadherin showed significant down-regulation in node-positive tumours compared to node-negative tumours when examined by IHC in 51 cases of breast cancer that included 29 node-negative and 22 node-positive cases.…”
Section: Diagnostic/prognostic Markersmentioning
confidence: 99%